"Focus in Your Study and Don't Worry": Exploring the Roles of Student Mother in Higher Education Institution in Malaysia - Siti Norzaimalina, Abd Majid (Secholian Publication PLT, 2010)
The role of a mother alone is very challenging. With an additional role as a student or a worker add more burden to them. It is undeniable that Malaysian women in the 21st century has more roles than women in the pre-independent era. Nowadays, women have equal opportunities to work and pursue higher education like men. The need to provide quality life to the children has also encouraged women to contribute more in the family income. Despite the multiple roles play by women, the household tasks are still managed by them. For this phenomenological research, in-depth interviews were conducted with two participants who studied in public university in Malaysia. By using thematic analysis, four themes were emerged from this study. The themes were challenges, role management, assistance/support and coping strategies. In this study, the major challenge was to balance the role of mother and student. But whatever challenges they faced; family was their priority. Furthermore, spousal support also helped the mothers in managing their multiple roles. From the findings, it is hoped that it gives some insights on the type of support that student mother needs and ways of coping in challenging situation.